Ocular Lesions in Birds of Prey in Portugal: A Retrospective Study - Lucas Ribeiro; Maria Casero; Carolina Nunes; Mariana Ribeiro; Roberto Sargo; Filipe Silva; Elisete Correia; Maria de Lurdes Pinto (Birds, 2024)
In wildlife rehabilitation centers, thousands of animals are treated annually, with a substantial proportion being birds of prey. Since vision is essential for the survival of these species, this study focused on investigating the causes of ocular injuries in raptors admitted to four rehabilitation centers across mainland Portugal from 2017 to 2021. Of the 2207 birds admitted during this period, 156 (7%) presented ocular injuries. Hyphema (28.2%) and corneal ulcers (20.5%) were the most prevalent injuries, often occurring together or alongside lens luxation. Nocturnal raptors showed a higher prevalence of these injuries (76.9%) compared to diurnal raptors (23.1%). A significant association was found between ocular injuries and causes of admission, particularly with ocular hemorrhages and multiple injuries in the eye. Despite the severity of the ocular injuries, the release rate remained relatively high at 51%, underscoring the critical role of comprehensive ocular examinations and vision assessments in guiding treatment decisions and discharge decisions. This study highlights the need for further research with larger samples to better understand the impact of ocular injuries on the rehabilitation success of wild birds in Portugal.